Something old, something new : college writing teachers and classroom change - Bishop, Wendy, 1953-2003.; Conference on College Composition and Communication (U.S.) (Carbondale : Southern Illinois University Press, 1990)
How do college writing teachers learn new ways to teach? Most current composition research focuses almost exclusively on student writers, ignoring the role the teacher plays in classroom development. Here is the first book to focus on college writing teachers and the ways in which they are affected by graduate rhetoric pedagogy courses. Wendy Bishop observed teachers enrolled in a doctoral seminar, titled ""Teaching Basic Writing,"" and then conducted case studies of five of those teachers in their college writing classrooms to investigate how their teaching practices changed and how their p.
1. Training teachers in a graduate program in rhetoric -- 2. Susan, a pre-college level teacher of writing : the challenge of the structured process classroom -- 3. Rosalyn, a pre-college level teacher of writing : grammar and the process classroom -- 4. Peg, a college level teacher of writing : individualized versus collaborative learning -- 5. Nick, a college level teacher of writing : the teacher at the center or the teacher at the side -- 6. Julia, a college level teacher of writing : transforming kids and students into writers and peers -- 7. College writing teachers and classroom change.
"Published for the Conference on College Composition and Communication."
Includes bibliographical references (pages 159-166).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching (Higher); LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching (Higher); Aufsatz; College; Englischunterricht; USA; Electronic books; Electronic books